Bridging community and prison for older adults: invoking human rights and elder and intergenerational family justice. Issue 1 (12th March 2014) - Maschi, Tina; Viola, Deborah; T. Harrison, Mary; Harrison, William; Koskinen, Lindsay; Bellusa, Stephanie
Abstract : Purpose: – Older adults in prison present a significant health and human rights challenge for the criminal justice system. To date, there is no known study that provides a comprehensive examination or portrait of older persons in prison. The purpose of this paper is to understand individual, family, system, and community vulnerabilities that can complicate successful community reintegration for these individuals. Design/methodology/approach: – This study provides a cross-sectional, descriptive analysis of biopsychosocial, spiritual, and prison use characteristics associated with a sample of 677 older prisoners, aged 50+, in a state-wide prison system. Findings: – Results indicate the extent of diversity within this population based on demographic, clinical, social, legal profiles, prison service use patterns, and professional and personal contacts. Research limitations/implications: – Due to the diversity within this population, an interdisciplinary approach is needed to address the complex social and health care needs of an aging prison population and to plan for their reentry. Practical implications: – These findings suggest the need for holistic prevention, assessment, and interventions to interrupt the social-structural disparities that foster and support pathways to incarceration and recidivism. Originality/value: – The human rights implications for the current treatment of older adults in prison include providing in-prison treatment that promotes safety, well-being, reconciliation, and seamless bridges between prison and community for older adults and their families. The True Grit Program is presented as an example of a humanistic and holistic approach of such an approach.